Quality Control of Fish Cracker Products Using Failure Mode and Effect Analysis (FMEA) Method in UD. Zahra Barokah - Mochammad Alfian Yazdad; Elly Ismiyah; Hidayat Hidayat (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2022)
Zahra Barokah is a company that produces fish crackers. The problem that occurs is the defective products is too high, 5.84% from the total production of 4535kg in June - August 2021. It lead to the costs increase and the company loses. In this study, the Failure Mode and Effect Analysis (FMEA) method is used to identify the factors that cause these problems, to minimize product defects and reduce losses. The results showed that from the three types of defects, the one that had the highest Risk Priority Number (RPN) was a knife on a blunt cutting machine. Suggested improvement recommendations based on the results of this study are: workers should carry out regular checks on the cutting machine; and provide understanding to workers regarding SOPs on cutting machines. UD. Zahra Barokah adalah perusahaan yang memproduksi kerupuk ikan. Permasalahan yang terjadi adalah tingginya jumlah produk cacat yang mencapai 5,84% dari total produksi 4535 kg pada bulan Juni - Agustus 2021. Sehingga biaya yang dikeluarkan bertambah dan perusahaan mengalami kerugian. Pada penelitian ini, metode Failure Mode and Effect Analysis (FMEA) digunakan untuk mengidentifikasi faktor-faktor yang menyebabkan terjadinya permasalahan tersebut sehingga dapat meminimalisir produk cacat dan mengurangi kerugian. Hasil penelitian didapatkan bahwa dari ketiga jenis cacat yang terjadi, penyebab yang memiliki nilai Risk Priority Number (RPN) tertinggi ialah pisau pada mesin pemotong tumpul. Rekomendasi perbaikan yang disarankan berdasar hasil penelitian ini adalah: pekerja harus melakukan pemeriksaan pada mesin pemotong secara berkala; dan memberikan pemahaman kepada pekerja terkait SOP pada mesin pemotong.